Precision Prevention through Social Media: Report of Four Cases - Gabarron, Elia; Lopez-Campos, Guillermo; Davies, Shauna; Chomutare, Taridzo; Tan, Iris Thiele Isip; Petersen, Carolyn (Yearbook of Medical Informatics, 2024)
Background: Precision prevention involves using biological, behavioral, socioeconomic, and epidemiological data to improve health for a particular individual or group. With almost 63% of the global population using social media, these platforms show promise to deliver tailored messaging and personalized interventions to individuals.Objectives: To describe the personalization elements and behavior components used in a sample of precision prevention interventions delivered through social media.Methods: To identify examples of cases, a search was done on clinicaltrials.gov, searching for ‘other terms: prevention’ + ‘Intervention/Treatment: social media intervention’ + ‘study results: With results. The selected cases were described, personalization elements reported, and their adopted intervention components were coded according to the Behavior Change Wheel (BCW) framework.Results: A total of four cases employing personalization in their interventions were identified. Three of these cases targeted women's health. The intervention period varied from two to eight months, with participant commitment ranging from active involvement on five out of seven days to monthly participation. The BCW interventions of persuasion and incentivization, were most frequently utilized, while education and coercion were used sparingly in the selected cases. Notably, none of the four cases reported the use of training, restrictions, or modeling.Conclusions: Social media has the potential to serve as a tool for digital phenotyping and contribute to the advancement of precision prevention. Challenges include the social media platform set-up and ensuring all ethical considerations are met.
Keywords: Social media; Prevention; Precision medicine; Internet-based intervention